Curating the truth, curating the lie: two content curation strategies against disinformation - Guallar, Javier; López-Borrull, Alexandre (Anuario ThinkEPI, 2022)
Two strategies are proposed for dealing with disinformation by using content curation, which we term "curating the truth" and "curating the lie." The former is the traditional concept of content curation, which seeks to optimize existing content of value. The latter is a curation process linked to supporting the debunking of hoaxes, rumors, and falsehoods. These two strategies are exemplified through four cases of curation posts on Twitter. Various implications are discussed, such as the identification of and access to the sources of hoaxes or the cost of each strategy.
Keywords: Content curation; Disinformation; Hoaxes; Fake news; Verification; Fact checking; Information sources; Social media; Twitter